Temporal trends in children pertussis burden in China and worldwide from 1990 to 2023: An analysis of the Global Burden of Disease Study 2023 - Beinan Xu; Jingjing Gu; Xiaolin Ye; Dongling Liu; Shangfu Xie; Yuanlin Lv; Yixuan Mou; Wei Wu (PLoS ONE, 2026)
Objective To evaluate the burden trends of children pertussis worldwide and in China from 1990 to 2023, and predict the disease burden for the next 10 years using a secondary analysis of Global Burden of Disease (GBD) 2023 data. Methods The primary metrics were mortality, disability-adjusted life - years (DALYs), prevalence, and incidence. A join – point regression model was used to estimate the average annual percentage change (AAPC). The autoregressive integrated moving average (ARIMA) model was used to predict the disease burden of pertussis from 2024 to 2033, and its adequacy was confirmed by the Ljung‑Box test. Results From 1990 to 2023, childhood pertussis mortality, DALYs, prevalence, and incidence declined sharply worldwide and in China. The global mortality rate in infants aged 1–5 months decreased by 57.7%, from 108.09 per 100,000 in 1990 to 45.73 per 100,000 population in 2023. Global age-standardized rates for both sexes, as well as those in all SDI regions, also showed steady downward trends. The rates of all four metrics peaked among infants aged 1–5 months in China and declined steadily with increasing age. For this infant group, the APC of pertussis prevalence and incidence in China decreased significantly during three different periods (1995–2004, 2009–2018, 2018–2021), but rose in two intervals (2004–2009, 2021–2023). ARIMA model projections revealed that age-standardized mortality and DALY rates will rise over the next decade, while prevalence and incidence will continue to decline. Notably, prevalence and incidence among infants aged 1–5 months are expected to increase slightly, rising from 277.59 and 2,026.43 per 100,000 in 2024 to 284.04 and 2,073.46 per 100,000 in 2033, respectively. Conclusion These findings underscore the disproportionate and persistent burden of pertussis in infants, indicating that prevention and treatment strategies should be adjusted to prevent further increase.